2004
DOI: 10.1002/pon.794
|View full text |Cite
|
Sign up to set email alerts
|

Then and now: quality of life of young breast cancer survivors

Abstract: Five years after diagnosis, young breast cancer survivors who remained cancer-free enjoyed good health and improved quality of life. Nonetheless, physical, social, and psychological concerns must be addressed so that young breast cancer survivors will continue to be resilient as they age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
313
6
23

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(373 citation statements)
references
References 53 publications
31
313
6
23
Order By: Relevance
“…However, breast cancer patients after diagnosis have poorer physical functioning in comparison with healthy controls [6][7][8][9], and more frequent malaise [10][11][12]. Furthermore, breast cancer patients feel more stress and anxiety about the future compared to the general population and have lower mental domain scores [13][14][15]. These findings suggest that the diagnosis and various treatments of breast cancer will affect the long-term HRQOL.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, breast cancer patients after diagnosis have poorer physical functioning in comparison with healthy controls [6][7][8][9], and more frequent malaise [10][11][12]. Furthermore, breast cancer patients feel more stress and anxiety about the future compared to the general population and have lower mental domain scores [13][14][15]. These findings suggest that the diagnosis and various treatments of breast cancer will affect the long-term HRQOL.…”
Section: Introductionmentioning
confidence: 80%
“…The most important task is to provide a social support system and rehabilitation for patients with long-term physical, mental and functional problems after cancer treatment, with the goal of improving long-term HRQOL, on which social support has a great effect [5,8,14,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Younger, premenopausal women seem to experience more distress, higher levels of depression, cope less well and report poorer quality of life than older women [8][9][10].…”
Section: Women's Experiences Of Breast Cancermentioning
confidence: 99%
“…Although, previous research has suggested that cancer survivors believe that healthy behaviors can prevent cancer recurrence, these studies have focused mostly on the quality of life and the adjustments made after cancer (Bloom et al, 2004;Rabin and Pinto, 2006;Costanzo and Ryff, 2009). Another study indicated that social support had a positive impact on cancer patients (Helgeson and Cohen, 2000).…”
Section: Breast Cancer Survivors' Efforts To Renew and Preserve Theirmentioning
confidence: 99%